Pembiasaan Karakter Religius Peserta Didik di MI Ma’arif Wotbuwono - Nurul Sabitussolikhah; Nurul Aulia Amrissadiah; Ibnu Jati Pramono; Muna Fauziah (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2026)
Religious character building is a strategy widely implemented in Islamic schools to internalize Islamic values ​​and shape positive behavior in students sustainably. This study aims to describe the forms of religious character building, its implementation mechanisms, the role of teachers, and its impact on the development of student behavior at MI Ma'arif Wotbuwono. The study used a qualitative approach with a descriptive design. Data were obtained through observation, interviews, and documentation involving the principal, teachers, and students. Data analysis was carried out interactively using the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and drawing and verifying conclusions. The results showed that religious character building was implemented systematically through greeting and handshake activities, Reading Tahfidz Al-Qur'an (RTQ) according to students' abilities, reading Asmaul Husana before learning, Duha prayer, scheduled tahlil, and congregational Zuhur prayer. The consistent implementation of these activities, supported by exemplary behavior and teacher guidance, contributes to the formation of religious character, discipline, responsibility, respect, and noble morals in students. This study shows that the success of religious character education is determined not only by routine activities but also by the formation of a madrasah culture that supports the continuous internalization of values. These findings provide empirical evidence regarding the implementation of religious character education in elementary madrasahs and can be used as a reference in developing character education programs in Islamic elementary schools.